Cancer mortality in the elderly in 11 countries worldwide, 1970–2015. (30th May 2019) - Carioli, G; Malvezzi, M; Bertuccio, P; Hashim, D; Waxman, S; Negri, E; Boffetta, P; La Vecchia, C
Abstract: Background: Population ageing results in an increasing cancer burden in the elderly. We aimed to evaluate time-trends in cancer mortality for adults aged 65 and over for 17 major cancer types and all cancers combined in 11 countries worldwide over the period 1970–2015. Materials and methods: We obtained cancer death certification and population figures from the WHO and PAHO databases. We computed age-standardised (world standard population) rates for individuals aged 65 and over, and applied joinpoint regression models. Results: Age-standardised mortality rates for all cancers combined showed a heterogeneous, but widespread decline. Lung cancer mortality rates have been decreasing among men, and increasing among women. Pancreatic cancer had unfavourable trends in all countries for both sexes. Despite variability across countries, other tobacco-related cancers (except kidney) showed overall favourable trends, except in Poland and Russia. Age-standardised mortality rates from stomach cancer have been declining in all countries for both sexes. Colorectal mortality has been declining, except in Poland and Russia. Liver cancer mortality increased in all countries, except in Japan, France and Italy, which had the highest rates in the past. Breast cancer mortality decreased for most countries, except for Japan, Poland and Russia. Trends for age-standardised uterine cancer rates in the USA, Canada and the UK were increasing over the last decade. Ovarian cancer rates showed declines in most countries. With the exception of Russia, prostate cancer rates showed overall declines. Lymphoid neoplasms rates have been declining in both sexes, except in Poland and Russia. Conclusion: Over the last decades, age-standardised cancer mortality in the elderly has been decreasing in major countries worldwide and for major cancer sites, with the major exception of lung and uterine cancer in women and liver, pancreatic and kidney cancers in both sexes. Cancer mortality for the elderly in central and eastern Europe remains comparatively high.